Prevalence of diabetes in New Zealand general practice: the influence of ethnicity and social deprivation. Issue 5 (11th February 2009) - Joshy, G; Porter, T; Le Lievre, C; Lane, J; Williams, M; Lawrenson, R
Abstract : Background: The prevalence of diagnosed diabetes among different ethnic groups and the influence of deprivation on the prevalence of diabetes among Māori and New Zealand Europeans was investigated. Methods: This was a cross-sectional survey on all patients registered with 10 practices in the Rotorua General Practice Group on 1 July 2007. Patients diagnosed with diabetes were identified though diagnostic codes for diabetes, prescriptions for diabetes medications and laboratory tests for glycosylated haemoglobin (HbA1c ). Prevalence of diabetes by ethnicity, age group, gender and NZDep2001 quintiles was calculated. Adjusted ORs for the risk of diabetes were obtained from logistic regression analysis. Results: Of the 45 500 patients registered, 1819 had been diagnosed with diabetes mellitus. In the 40+ age groups, the prevalence of diabetes in Māori and Pacific people was around three times that in Europeans. With increasing deprivation, the age-standardised prevalence of diagnosed diabetes increased among European males (2.7–5.0%) and females (2.1–3.1%). However, the prevalence of diabetes was highest among the least deprived Māori (males 9.7%, females 6.2%). The adjusted risk of diabetes for the most deprived Māori is not significantly different from that for the least deprived Māori. The most deprived Europeans had nearly twice the risk of having diabetes than the least deprived Europeans. Conclusions: Although the rising prevalence of diabetes with increasing deprivation among Europeans shows a similar trend to results from national and international studies, the trend among Māori seems to be different because the least deprived are equally at risk of diabetes. Diabetes interventions aimed at Māori should be tailor-made to include the least deprived groups.